Tenampúa: the fortress that transformed power in Central Honduras towards the Terminal Classic - Deras, Kesia (2025)
The terminal classic period was a time of profound social transformations that affected both Mesoamerica and its surrounding areas. In the central region of Honduras, the emergence of the Tenampúa fortress (CM-1), located southeast of the Comayagua Valley, consolidated a new regional center that drove a process of reorganization, changing local dynamics between the 9th and 10th centuries CE. This article presents a synthesis of the available data on the site, which allows for identifying how local populations adopted more centralized forms of organization in response to changing social and environmental conditions. It is argued that Tenampúa played a strategic role in the concentration of political and control functions during the transition from the Classic to the Postclassic period, establishing a model that until then had only been observed in the organization of the first states. Integrating this information contributes to a better understanding of social change dynamics in frontier zones, highlighting how groups southeast of the border between Mesoamerica and the Isthmo-Colombian Area reorganized in response to these changes, a topic that until recently had received little attention in the archaeological research of the region. Finally, the need for more systematic studies in emphasized to advance knowledge of these processes.